Psychoeducation In Adolescent Offenders: Compliance With A Socioeducational Measure In Huánuco - Acencio Malpartida, Larry F. (2024)
This research has been directed from the socio-critical paradigmatic position, with a qualitative methodology, it has been involved from an action research design with the emancipatory critical approach, as defined by Carr and Kemmis (1988), with the purpose of knowing the way In how adolescent offenders experience their experiences while they participate in a tax manner in the psychoeducational intervention of their socio-educational measure, from what was analyzed it has been possible to emerge a relationship of trust and mutuality of these actions that has fostered among the participants while the stage of recognition, planning, execution and reflection, these types of actions are defined under the necessary scientific rigor of a social research study, the versions were the ACLP who intentionally participated in the company of their parents and guardians, as well as the members of the technical team of SOA Huánuco professionals, the data has been They have been able to consolidate through social work mechanisms such as interviews, discussion groups and team meetings that were carried out remotely in Messenger rooms, the same ones that were captured through audio recording applications, later has carried out a categorization and coding process in an open, axial and selective way, the intervention of the participants favored the triangulation of information that receded into categories, and with this it has been possible to obtain a level of detailed understanding in the different moments of the experience that the adolescent and his environment understand, but it has also been possible to carry out the analysis of the context on how the offending adolescent evolves and reflects.